2017
DOI: 10.1021/acs.est.7b02752
|View full text |Cite
|
Sign up to set email alerts
|

Oral Exposure to Silver Nanoparticles or Silver Ions May Aggravate Fatty Liver Disease in Overweight Mice

Abstract: As the applications and environmental release of silver ions and nanoparticles are increasing, increasing human exposure to these pollutants has become an emerging health concern. The impeding effects of such pollutants on susceptible populations are severely under-studied. Here, we demonstrate that silver nanoparticles (Ag NPs), at a dose that causes no general toxicity in normal mice, promotes the progression of fatty liver disease from steatosis to steatohepatitis only in overweight mice. Exposure to Ag ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 60 publications
(86 reference statements)
0
57
0
Order By: Relevance
“…24 Similarly, oral exposure to silver NPs promoted progression from steatosis to steatohepatitis in overweight mice. 25 In contrast, cerium oxide NPs were found to reduce steatosis and display anti-inflammatory properties in liver-fibrosis rats. 26 However, the possible mechanisms of steatosis induced by NPs were unclear.…”
Section: Discussionmentioning
confidence: 99%
“…24 Similarly, oral exposure to silver NPs promoted progression from steatosis to steatohepatitis in overweight mice. 25 In contrast, cerium oxide NPs were found to reduce steatosis and display anti-inflammatory properties in liver-fibrosis rats. 26 However, the possible mechanisms of steatosis induced by NPs were unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that hypertension intensified AgNP-induced cardiotoxicity due to an observed reduction in NO and an increase in oxidative stress, leading to increased vasoconstriction and myocardial contractility. Jia et al [210] studied the effect of orally-exposed PVP-AgNPs (30 nm) in overweight mice and showed the progression of fatty liver disease from steatosis to steatohepatitis. The mechanisms proposed in the latter study were the activation of Kupffer cells, the enhancement of hepatic inflammation, and the suppression of fatty acid oxidation.…”
Section: Knowledge Gaps In Human and Environmental Risk Assessmentmentioning
confidence: 99%
“…Recently, dissolved and nano-silver had been quantitated in organ lysates [ 18 ]. These studies suggested that after intravenous application, Ag-NP were mostly, but not exclusively, gathered in the liver [ 19 ], from where they were released into other organs where they were detectable as ions. Due to a disturbed liver metabolism, the authors suggested that silver NP toxicity was related to Ag-NP rather than to silver ions, a view substantiated by the finding that damage of endothelial cells and subsequent permeation through epithelial barriers is caused by Ag-NP rather than Ag ions [ 18 ].…”
Section: Introductionmentioning
confidence: 99%